Individual meaning of Impulsive Buying: Phenomenological study on Wearing Klamby Instagram Account - Herdianti Sari, Rizky; Lorita Simamora, Santa; Budi Sulistyo, Ponco (Universitas Ahmad Dahlan, 2025)
This research aims to analyze and describe the experience of impulsive buying behaviour among followers of the Wearing Klamby Instagram account through a phenomenological perspective. This research uses an interpretive paradigm with a qualitative approach to understanding the motivation, goals and subjective meaning of shopping among account followers. The research results show that the experience of purchasing behaviour in the context of followers of the Wearing Klamby Instagram account is influenced not only by individual elements but also by the social dynamics in the online community. The phenomenological analysis also finds that purchasing behaviour is driven not only by functional but also by emotional and social needs. This research gives marketers insight into the importance of building deeper relationships with consumers through social media and prioritizing values relevant to the target audience.